A General Equilibrium Evaluation of Aggregate Welfare Effects from Improved Sectoral Efficiency. Empirical Evidence for Norway - Erling Holmøy (Statistics Norway, Research Department, 1998)
This paper discusses and shows how a CGE model can be used to assess welfare effects of structural policy reforms targeting inefficiency problems at micro levels that normally are not captured in operational CGE-models. The CGE approach allows computation of shadow prices which are generally both unobservable due to various price distortions, and endogenous. Moreover, the paper discusses how static measures of sectoral inefficiency can be implemented in a CGE-model that accounts for real world dynamics. Results from CGE-simulations suggest that general equilibrium effects have substantial influence on welfare, at least when the initial waste of resources is as large as reported in sector studies for Norway. More precisely, compared to the CGE-estimate a partial equilibrium approach overestimates the welfare gain by more than 30 percent.
Keywords: C68; C81; H50; L70; L98; 330; Structural reform; Efficiency gains; General equilibrium effects